PARADIPLOMASI PEMERINTAH KOTA JAKARTA PADA C40 CITIES CLIMATE LEADERSHIP GROUP 2018-2020 - Audi Zulfa Sholihan (2022)
Today, awareness and attention to climate change and problems is increasing, such as globalization and global industrialization, which have more or less had a real impact and risk on the lives of living things on earth. Solving climate change at the sub-national level as a technical actor and directly addressing the problem, is considered more optimal by implementing national and international policies which are then applied directly. The city of Jakarta has been part of the C40 Cities Climate Leadership Group global city network since 2006, committed to taking sustainable urban climate action. This study aims to find out the Paradiplomacy of the Jakarta City Government in the C40 Cities Climate Leadership Group for the period 2018-2019. Data were collected through interviews and literature as primary and secondary data sources. This research uses the concept of Paradiplomacy and Multi-Level Governance. The results of this study explain the Paradiplomacy of the Jakarta City Government at C40 through cooperation in several ways, legalizing commitments, hosting the Climate Action Plan program initiation meeting in Southeast Asia, declarations, and Jakarta as the Steering Committee